Bio-Conversion and Decomposing With Black Soldier Fly to Promote Plant Growth - Susanto, Markus; Kurniawan, Setya; DEP, Ricardi; Rianne, Widya; Hersade, Devide (KnE Life Sciences, 2022)
Every country in the world, including Indonesia, is confronted with the problem of waste and is attempting to find viable solutions. The majority of recycled waste is inorganic waste, while there is also organic recycled waste, and the remaining 60-75%of waste is dumped in a landfill. By utilizing waste and by-products, bioconversion with black soldier fly (BSF) larvae could be a solution to help overcome the problem of organic waste; these larvae can also be used as a protein source in animal feed and in organic fertilizers rich in nutrients. The use of BSF as a decomposer of organic waste, specifically Black Soldier Fly Fertilizer (BSF Frass), and the liquid resulting from the bioconversion process, called micro biostimulant (MBS), can be used to promote plant growth. The goal of this study was to assess how BSF Frass affected plant growth when compared to Synthetic fertilizers. Corn and Pak Choi were the test plants that were planted in the field. The results showed that giving 50% BSF Frass to the tested plants resulted in better growth and development than the control. Keywords: Bioconversion, Organic Fertilizer, Black Soldier Fly Compost, Frass.